Человеческий фактор в обеспечении безопасности функционирования электростанций - Dmitriev, П. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
It is shown in the article that the components of a human factor which are characteristic to a human controller and which influence on the safeguarding of security of the functioning of the power stations are the fundamental psychological qualities that are significant to a professional. These qualities are: distribution and changeover of attention, operation thinking and logical thinking. These results are based on the psychological researches that were carried out among the operators of a boiler and turbine workshop of the Mogilev heat station. The importance of the foregoing basic psychological qualities, that are significant to a professional in the activities of the operators of the heat station, is revealed. This article is advised to the specialists of the power system of the Republic of Belarus that examine the question of the safeguarding of security of the functioning of the power stations.